Comparative Seeds Storage Transcriptome Analysis of Astronium fraxinifolium Schott, a Threatened Tree Species from Brazil - Pereira Neto, Leonel Gonçalves (2022)
Astronium fraxinifolium Schott (Anacardiaceae), also known as a ‘gonçalo-alves’, is a tree of the American tropics, with distribution in Mexico, part of Central America, Argentina, Bolivia, Brazil and Paraguay. In Brazil it is an endangered species that occurs in the Cerrado, Caatinga and in the Amazon biomes. In support of ex situ conservation, this work aimed to study two accessions with different longevity (p50) of A. fraxinifolium collected from two different geographic regions, and to evaluate the transcriptome during aging of the seeds in order to identify genes related to seed longevity. Artificial ageing was performed at a constant temperature of 45 °C and 60% relative humidity. RNA was extracted from 100 embryonic axes exposed to control and aging conditions for 21 days. The transcriptome analysis revealed differentially expressed genes such as Late Embryogenesis Abundant (LEA) genes, genes involved in the photosystem, glycine rich protein (GRP) genes, and several transcription factors associated with embryo development and ubiquitin-conjugating enzymes. Thus, these results contribute to understanding which genes play a role in seed ageing, and may serve as a basis for future functional characterization of the seed aging process in A. fraxinifolium.